Procyclicality of Financial Systems in Asia - Gerlach, Stefan (International Monetary Fund, 2006)
The procyclicality of financial systems has received an increasing amount of attention from policymakers, academics, and international organizations in recent years. This heightened interest stems from a combination of the ongoing globalization of finance, the role of the financial sector in various emerging market crises in the late 1990s, and the potential impact on financial sectors of the upcoming implementation of the Basel II accord. Some degree of financial sector procyclicality is a characteristic of any normally functioning economy. At issue is whether the observed procyclicality is excessive. The challenge is to define "excessive" and to identify policy measures that could produce superior economic outcomes. This volume attempts to do so by collecting recent work on procyclicality in Asian financial systems. For more information on how to purchase a copy of this title, please visit http://www.palgrave.com/economics/imf/index.asp.